Analisis realisasi Anggaran Belanja Daerah Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Dan Tenaga Kerja Kota Sawahlunto Tahun 2016-2020 - Sophan Sophian; Vaulya Rezi (LPPM Universitas Dharma Andalas, 2022)
The low ability of the goverment to explore potential sources of PAD makes the goverment always depend on central goverment funds. The purpose of study is to determine the financial perfomance of the office of investment,one stop service and manpower Sawahlunto City in 2016-2020 by using ratio analysis effectiveness and efficieny ratio. The type of research used is descriptive quantitative research,the result of this study conclude that the effectiveness ratio is very effective while the efficiency ratio is quite efficient.